MULTIELEMENT DETERMINATION IN METHANOLIC SOXHLET LEAF EXTRACT OF SEMECARPUS ANACARDIUM (LINN.F.) BY ICP-AES TECHNIQUE - Pednekar, Parag A.; Raman, Bhanu (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Abstract Objective: Multielement analysis was carried out on methanolic soxhlet leaf extract of Semecarpus anacardium using the ICP-AES technique. Methods: ICP-AES technique is one of the most powerful and quick multi elemental analysis with high sensitivity. 41 elements Na, Mg, Si, Cl, K, Ca, Cr, Mn, Fe, Ni, Cu, Zn, Co, Cd, Se, Al, S, Pb, Ba, Hg, As, B, P, Sr, Br, Ti, Bi, Ge, In, La, Li, Mo, Pd, Sb, Sc, Sn, Te, V, W, I, Th were screened. Results: 12 elements were detected out of 41 elements in the above plant in various proportions depending on soil composition and the climate in which the plant grows. Conclusion: The elements present in the medicinal plant plays an important role in the treatment of diseases as described in Ayurveda. The methanolic soxhlet leaf extract of Semecarpus anacardium showed the presence of essential elements that could enhance the curative process of ill health and the potentially toxic elements were not detected in the present plant extract. Key words: ICP-AES, multielement analysis, Semecarpus anacardium (Linn.F.), Ayurveda. Â